EFL Students’ Perception on Kahoot! as Alternative Learning Strategy to Improve Reading Comprehension Skill - Meli Fauziah; Renggi Vrika; Amrullah Amrullah (Universitas Muhammadiyah Barru, 2024)
Kahoot! has gained popularity for boosting motivation, improving classroom engagement, and supporting collaborative learning over the past few years. The purpose of the study was to find out how EFL students’ perception about using Kahoot! as an alternative learning strategy to enhance their reading comprehension skills. This study uses a descriptive design and is quantitative in nature. The participants in this study were 65 students coming from three classes of the third semester students of English Tadris Study Program IAIN Curup. The sampling approach employed was total sampling, meaning a sample of every population was taken. After using Kahoot! as a learning tool, the students were given a closed-ended questionnaire using a Likert scale. To process the data, descriptive statistical analysis was employed. The average proportion, according to the questionnaire's results, was 78,44%. According to this proportion, students' opinions about using Kahoot! as an alternative learning strategy to enhance their reading comprehension skill was classified as positive perception. Additionally, it is possible to draw the conclusion that Kahoot! has impacted students' reading comprehension and can aid in their improvement.